BEHAVIOR ANALYSIS OF SPORTING GOODS CONSUMERS - Maria-Daniela; Álmos ANDRÁS; Simion Gheorghe MERCHEȘ (Cluj University Press, 2016)
The actual aims of this paper is to study and analyze the consumer's behavior regarding sports articles, which represent a relatively new area of studying all over the world and especially in our country. At the beginning of the sports products and services development, the countries and the organizations that were acting on this market and in these countries have noticed the necessity of applying the marketing elements and products, but also the studying of these ones in order to find out the consumer's preferences, so that their business can develop, grow and lead to a worldwide evolution of this domain. This study wants to develop a sports marketing strategy, based on the previous support of studying and analysis of the sports articles, but also based on the needs of the customer of these products and the identification of the primarily elements that stand for the base of influencing the customer's behavior when buying sports articles and products. Our objectives are the following: to identify the interest for sports products and articles inside the group; the preferences of the targeted group regarding the brand of sports products and articles-most wanted; the setting of the category from which most customers buy sports products and articles. Analiza comportamentului consumatorilor de articole sportive. Prin prezenta lucrare se urmărește studierea și analiza comportamentul consumatorului de produse sportive, care reprezintă un domeniu de studiu relativ tânăr în lume și în special în țara noastră. La începutul dezvoltării pieței de produse și servicii sportive, țările și organizațiile ce activau pe această piață și în aceste țări au observat necesitatea punerii în aplicare a elementelor și produselor de marketing precum și studierea acestor în vederea aflării cerințelor de pe piață, astfel încât afacerea lor să se dezvolte, să ia amploare și implicit să ducă la o evoluție de ansamblu a domeniului. Prezenta lucrare își propune dezvoltarea unei strategii de marketing sportiv, realizată pe fondul studiului și analizei prealabile a pieței de produse și articole sportive, precum și a nevoilor consumatorului de aceste produse și identificarea factorilor primordiali ce stau la baza influențării comportamentului consumatorilor în achiziționarea de articole și produse sportive. Ca și obiective ne-am propus următoarele: identificarea interesului pentru produsele și articolele sportive în cadrul grupului; opțiunea grupului țintă referitor la marca de produse și articole sportive cea mai căutată; stabilirea categoriei de consumatori ce achiziționează cel mai mult articole și produse.  Cuvinte cheie: articole sportive, consumator, comportamentul consumatorului